Mimicry of Short Linear Motifs by Bacterial Pathogens: A Drugging Opportunity. Issue 6 (June 2020) - Sámano-Sánchez, Hugo; Gibson, Toby J.
Abstract : Bacterial pathogens have developed complex strategies to successfully survive and proliferate within their hosts. Throughout the infection cycle, direct interaction with host cells occurs. Many bacteria have been found to secrete proteins, such as effectors and toxins, directly into the host cell with the potential to interfere with cell regulatory processes, either enzymatically or through protein–protein interactions (PPIs). Short linear motifs (SLiMs) are abundant peptide modules in cell signaling proteins. Here, we cover the reported examples of eukaryotic-like SLiM mimicry being used by pathogenic bacteria to hijack host cell machinery and discuss how drugs targeting SLiM-regulated cell signaling networks are being evaluated for interference with bacterial infections. This emerging anti-infective opportunity may become an essential contributor to antibiotic replacement strategies. Highlights: Bacterial pathogens can secrete proteins containing mimics of host SLiMs. Mimics of SLiMs can interfere with host PPIs or with host enzymes, altering the host environment for the benefit of the pathogen. Drugs targeting SLiM-regulated cell signaling networks can interfere with the progress of bacterial infection.